In situ formation of a 3D core-shell and triple-conducting oxygen reduction reaction electrode for proton-conducting SOFCs - Zhang, Z.; Wang, J.; Chen, Y.; Tan, S.; Shao, Zongping; Chen, D. (Elsevier SA, 2018)
BaZr x Ce y Y 1-x-y O 3-δ are recognized proton-conducting electrolyte materials for proton-conducting solid oxide fuel cells (H + -SOFCs) below 650 °C. Here Co cations are incorporated into the BaZr 0.4 Ce 0.4 Y 0.2 O 3-δ (BZCY) scaffold to generate a 3D core-shell and triple-conducting (H + /O 2− /e − ) electrode in situ via infiltrating and reactive sintering. The core is the bulk BZCY scaffold, while the shell is composed of the cubic Ba(Zr 0.4 Ce 0.4 Y 0.2 ) 1-x Co x O 3-δ , cubic spinel Co 3 O 4 and cubic fluorite (Ce, Zr, Y)O 2 . The obtained electrode exhibits an excellent compatibility with the BZCY electrolyte, and performs well in yielding a low and stable polarization resistance for oxygen reduction reaction for intermediate-temperature H + -SOFCs. In particular, it achieves polarization resistances as low as 0.094 and 0.198 Ω cm 2 at 650 and 600 °C in wet air (3% H 2 O) when the sintering temperature for the electrode is 900 °C. In addition, a symmetrical cell also exhibits operation stability of 70 h at 650 °C. Furthermore, a fuel cell assembled with the 3D core-shell and triple-conducting electrode delivers a peak power density of ∼330 mW cm −2 at 650 °C. The substantially improved electrochemical performance and high stability are ascribed to the unique core-shell structure and the formation of Ba(Zr 0.4 Ce 0.4 Y 0.2 ) 1-x Co x O 3-δ in the shell.